Do Pelvic Organ Prolapse Quantification Examination Ba and D Guide the Selection of Operation for Severe Pelvic Organ Prolapse? - Chunbo Li; Huimin Shu; Zhiyuan Dai (Journal of Investigative Surgery, 2020)
Purpose: To determine whether the preoperative Ba and D point could help to guide the choice of surgical procedure for POP. Materials and Methods: This prospective cohort study included 250 subjects with anterior/apical defect from January 2012 to June 2015. All subjects underwent a complete preoperative evaluation and completed 12 months of follow-up. Based on the connection of preoperative Ba and D point of Pelvic Organ Prolapse Quantification (POP-Q), patients were assigned two groups: 137 patients who underwent anterior vaginal repair with mesh (AVM) and 113 patients who underwent AVM combined with sacrospinous ligament fixation (SSLF). The primary outcomes were anatomical cure and recurrence rate of both procedures. Secondary outcomes were prolapse symptom, quality of life and sexual function based upon validated questionnaires. The complications were also recorded in both groups. Results: Both groups were homogeneous preoperatively. The anatomical success rates for the anterior, apical and posterior vaginal compartments were 99.2%, 97.0% and 97.7% in the AVM group, respectively. For patients who underwent AVM-SSLF, the anatomical success rates for the anterior, apical and posterior compartments were 96.1%, 98.1% and 98.1%, respectively. The recurrence for both techniques was low. Both procedures presented a significant improvement with regard to postoperative quality of life (QOL), prolapse symptoms, and sexual function after 1-year follow-up. Conclusion: The preoperative Ba and D point correlated with surgical choice for the treatment of anterior/apical prolapse, which further decided the surgical outcomes for prolapse support.